EFEKTIVITAS KOMBINASI TERAPI HANDGRIP EXERCISE DAN RANGE OF MOTION (ROM) TERHADAP KEKUATAN MUSKULAR EKSTREMITAS ATAS PASIEN PASCA STROKE NON-HEMORAGIK - Wavi Nurul Izzati; Dewi Suryandari; Wahyuningsih Safitri (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Non-hemorrhagic stroke is a neurological disorder caused by obstruction of blood flow to the brain, resulting in neuronal damage and decreased motor function, particularly upper extremity muscle weakness. This weakness limits patients’ daily activities, necessitating appropriate rehabilitative interventions. The combination of Hand Grip Strength and Range of Motion (ROM) exercises is believed to improve muscle strength through neuromuscular stimulation and increased muscle elasticity. Objective: This study aimed to determine the effect of combined Hand Grip Strength and ROM exercises on upper extremity muscle strength in non-hemorrhagic stroke patients at Dr. Moewardi Hospital, Surakarta. Methods: A pre-experimental design with a pre-test and post-test approach without a control group was used. A total of 44 respondents were selected using accidental sampling. The intervention was administered twice daily for 10–15 minutes over three consecutive days. The Manual Muscle Testing (MMT) scale was used to measure muscle strength. Results: The findings revealed a significant improvement in muscle strength after the intervention, with p < 0.05. These results support that combining Hand Grip Strength and ROM exercises effectively enhances upper extremity muscle strength in non-hemorrhagic stroke patients. Conclusion: There was a significant effect of the combination of ROM and Hand Grip Strength exercises on improving upper extremity muscle strength among non- hemorrhagic stroke patients at Dr. Moewardi Hospital (ρ = 0.000 < 0.05). This study is expected to serve as a reference for rehabilitative nursing interventions and contribute to preventing permanent disability in stroke patients.